2018
DOI: 10.1002/jrs.5494
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman scattering microscopy with long wavelengths for improved imaging depth

Abstract: Stimulated Raman scattering (SRS) imaging is a fast, label‐free, and sensitive technique to map the distribution of a vibrational species in a microscopy setting. It has great potential for applications in many fields, such as lipid imaging in biomedicine. However, depth penetration of the light into the sample is an issue with any light‐based technique, especially with multiphoton techniques such as SRS. Using longer wavelengths allows deeper penetration into densely scattering materials, but applying wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Moreover, the frequency of the NIR laser usually does not correspond to an electronic transition of the sample, thus diminishing possibility for the occurrence of fluorescence. Finally, use of longer Raman excitation wavelengths can significantly increase penetration depth, compared to shortwavelength lasers, thus more comprehensive information on pollen composition could be obtained (Moester et al, 2019). However, these important advantages of FT-Raman spectrometers can be overshadowed by sensitivity advantage of dispersive Raman spectrometers with short-wavelength laser excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the frequency of the NIR laser usually does not correspond to an electronic transition of the sample, thus diminishing possibility for the occurrence of fluorescence. Finally, use of longer Raman excitation wavelengths can significantly increase penetration depth, compared to shortwavelength lasers, thus more comprehensive information on pollen composition could be obtained (Moester et al, 2019). However, these important advantages of FT-Raman spectrometers can be overshadowed by sensitivity advantage of dispersive Raman spectrometers with short-wavelength laser excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Additional uncertainty about the quantification of silicone arises from the SRS depth resolution. In a previous study, we showed the full‐width‐at‐half‐max focal length in the Z‐dimension to be around 2.6 μm at similar wavelengths , which is about half of the 5 μm thick histological slides. This means that some silicone can be outside of the focal volume range and will not contribute to the SRS signal.…”
Section: Resultsmentioning
confidence: 74%
“…However, using epi geometry, this approach can also be used on thicker samples. In an earlier paper , we showed the feasibility of SRS imaging up to tens of micrometers in depth, at the expense of a lower signal‐to‐noise ratio. SRS being a nonlinear technique, it offers a sharp focus in the Z‐dimension and is therefore also suitable for 3D imaging through optical sectioning .…”
Section: Resultsmentioning
confidence: 99%
“…The SRS microscopy setup was mainly as described previously and is shown in Figure . Briefly, a frequency‐doubled Nd:YAG laser (Plecter Duo, Lumera) with 80 MHz repetition rate, 8 ps pulses, and 532 nm output pumps an optical parametric oscillator (OPO, Levante Emerald, APE) with 790–950 nm tunability range.…”
Section: Methodsmentioning
confidence: 99%
“…The light was collected with a water immersion condenser (NA = 1.2) below the sample, after which the 1,064‐nm beam was blocked. The stimulated Raman loss signal was detected at the OPO wavelengths with a photodetector (DET36A, Thorlabs) integrated with a home built trans‐impedance amplifier, reaching shot noise limited detection . The signal was demodulated with a lock‐in amplifier (HF2LI, Zurich instrument) with 100 μs time constant and used to reconstruct images with the microscope software (ZEN2011).…”
Section: Methodsmentioning
confidence: 99%